The MNC as an agent of change for host-country institutions: FDI and corruption - Kwok, Chuck C Y; Tadesse, Solomon (Journal of International Business Studies, 2006)
Most empirical research examines how the institutional environment of corruption shapes the behavior of multinational corporations (MNCs). In this study, we would like to highlight the other side of the picture: how the presence of MNCs may shape the institutional environment of corruption over time. We propose three avenues through which the MNCs may have an impact on its host institutions: regulatory pressure effect, demonstration effect, and professionalization effect. Based on extensive data on foreign direct investment and corruption for a large sample of countries over the last 30 years, the empirical results are generally consistent with our hypothesis. Such findings provide a glimmer of hope for the future of the host country where corruption is prevalent.